Hanönü (Kastamonu)-Günlüburun Karaçam (Pinus nigra Arnold. subsp. pallasiana (Lamb.) Holmboe) Tohum Bahçesinde Bazı Klonların Kozalak ve Tohum Özellikleri - Çılgın, Şahin; Ayan, Sezgin; Sıvacıoğlu, Ahmet; İktüeren, Şem'i (Kastamonu Üni., Orman Fakültesi Dergisi, 2007)
In this study, clonal variation was investigated in 9 years old Anatolian Black pine clonal seed orchard at Kastamonu-Hanönü based on cone, seed and seedling traits. For this aim, on 30 of clones, cone numbers (CoN) and cone holding percentage (CoHP) and on 9 of clones chosen randomly, cone weight (CoW, g), cone length (CoL, mm), cone width (CoWi, mm), number of seeds in one cone (CoSN), weight of thousand seeds (WTS), germination speed (GS), germination percentage (GP), cotyledon number (CN), hypocotyl length (HL) and root length (RL) were determined. The CoHP and CoN of the clones are 23.5 % and 78.1, respectively. There are significant difference among the clones and ramets as to the CoW, CoL, CoWi, GS, GP, HL and RL. The difference among the clones is 7.620-16.680 g for CoW, 44.275 - 64.475 mm for CoL, 23.370-31.135 mm for CoWi, 31.525-50.585 % for GS, 50.921-63.083 % for GP, 47.875- 65.563 mm for HL, 53.188-66.188 mm for RL. Also this values among the ramets are change 6.504-19.380 g for CoW, 40.560-68.360 mm for CoL, 22.380-31.800 mm for CoWi, 25.650-57.128 % for GS, 43.994-64.325 % for GP, 45.500-68.000 mm for HL, 49.500- 69.250 mm for RL. In point of CoSN, CoN and WTS there is only difference among the clones. And these values are change 2.0–24.0 number for CoSN, 16.930–25.617 g for WTS, 7–10 unit for CN. The result that bigger clonal variation among the ramets than the clones is supported by the another studies. There are significant relations between the CoL-CoW (R 2 = 0.9065), CoW-CoWi (R 2 = 0.7801), CoW-CoSN (R 2 = 0.571), CoL-CoWi (R 2 = 0.5688), CoL-CoSN (R 2 = 0.5536), CN-RL (R 2 = 0.5721) in the result of correlation analysis. In conclusion, clonal variation is determined for 12 of parameters except for cone numbers based on cone, seed and seedling traits of 9 years old Anatolian Black pine seed orchard.
Keywords: Anatolian black pine, Seed orchard, Cone, Seed